A prospective, comparative study of severe neurological and uncomplicated hand, foot and mouth forms of paediatric enterovirus 71 infections. (June 2017) - Crabol, Yoann; Pean, Polidy; Mey, Channa; Duong, Veasna; Richner, Beat; Laurent, Denis; Santy, Ky; Sothy, Heng; Dussart, Philippe; Tarantola, Arnaud; Buchy, Philippe; Horwood, Paul F.
Abstract: Objectives: In this study, we document the clinical characteristics and investigated risk factors for uncomplicated and severe forms of EV-A71 disease in Cambodian children. Methods: From March to July 2014 inclusive, all patients with suspicion of EV-A71 infection presenting to Kantha Bopha Hospitals in Phnom Penh and Siem Reap and confirmed by the Virology Unit at the Institut Pasteur du Cambodge were prospectively enrolled in this study. Throat swabs, rectal swabs and serum samples were collected from all consecutive patients with suspected EV-A71 infection. In addition, CSF was also collected from patients with suspected EV-A71 associated encephalitis. A total of 122 patients (29 with uncomplicated disease and 93 with severe disease) with confirmed EV-A71 infection with all available demographic and clinical data for clinical classification and further analysis were included in the study. Results: In this prospective EV-A71 study in Cambodia, we confirmed the previously reported association of male gender and absence of mouth or skin lesions with severe disease. We also highlighted the strong association of neutrophils in blood, but also in CSF in patients with pulmonary oedema. More importantly, we identified new putative nutrition-related risk factors for severe disease. Conclusions: EV-A71 is an important cause of encephalitis in the Asia-Pacific region. Further studies to determine the risk factors associated with severe EV-A71 disease are needed.